Concise review of the brown algal genus Padina (Dictyotaceae): knowledge in biodiversity, biogeography, potential and scope future research for Vietnam - Nguyen, Linh Manh; Akita, Shingo; Cao, Luong Van; Nguyen, Anh Thi Mai; Pham, Quang Van; Vu, Hung Manh; Nguyen, The Duc; Nguyen, Vy Xuan; Nguyen, Quan Van; Vieira, Christophe (Vietnam Journal of Marine Science and Technology, 2024)
The review critically examines the brown algal genus Padina (family Dictyotaceae), emphasizing its biodiversity, distribution, and potential applications, particularly in Vietnam. Globally, Padina species inhabit tropical and temperate coastal ecosystems, playing crucial ecological roles in primary production and as habitats for marine organisms. In Vietnam, nine species of Padina have been documented, yet their taxonomic diversity and applications remain underexplored. This synthesis highlights the morphological traits, ecological significance, and geographic distribution of Padina in Vietnam, with a focus on its potential in pharmaceuticals, nutraceuticals, cosmeceuticals, and bioremediation. Biochemical analyses reveal bioactive compounds such as terpenoids, polyphenols, and fucoidans, which demonstrate antioxidant, antimicrobial, and anti-inflammatory activities. These properties underscore Padina’s potential for natural product development in pharmaceutical and cosmetic industries. Despite this promise, research in Vietnam has predominantly centered on taxonomic and ecological aspects, with limited studies on biochemical and economic applications. The review identifies critical gaps in understanding species boundaries, phylogenetic relationships, and ecological roles. It advocates for advanced morphological and molecular studies, including molecular barcoding, to uncover cryptic diversity and resolve taxonomic ambiguities. Future research directions include exploring Padina’s reproductive biology, dispersal mechanisms, and responses to environmental stressors such as climate change. Additionally, investigations into its ecological roles, particularly as bioindicators of environmental health and agents for pollution mitigation, are essential. Addressing these gaps will enhance knowledge of Padina biodiversity and support the sustainable management and utilization of this valuable marine resource in Vietnam.